PELAKSANAAN PENGALAMAN LAPANGAN INDUSTRI (PLI) MAHASISWA D4 MANAJEMEN PERHOTELAN DI HOTEL HW KOTA - Setiani, Rini; Elida, Elida; Suyuthie, Hijriyantomi (Journal of Home Economics and Tourism, 2015)
The purpose of this reseach is to describing the implementation On The Job Training (OJT) of D4 Hotel Manajement student at HW hotel Padang. The result of previous survey indicate that the implementations of OJT Hotel Management student has not been conducted well. The type of research is descriptive qualitative. The informant where from Officers of Industrial relation Unit, coordinator OJT at the Home Economic Departement, Lecture as The Academic Supervisor, HW Hotel supervisor, and Hotel Management student that already finish OJT. The analisis technique this reseach are data reduction, data presentation, and deduction. The result of that search is that during OJT show knowledge jobs, quality of work, attitude, study skills, collaboration with collagues, the ability to follow safety procedures are good but initiative at work, dicipline, absent are poorly and need to be increase.Key Word : On the Job Training